Income and Well-Being: Relative Income and Absolute Income Weaken Negative Emotion, but Only Relative Income Improves Positive Emotion - Yu, Zonghuo; Chen, Li (Frontiers in Psychology, 2016)
Whether relative income or absolute income could affect subjective well-being has been a bone of contention for years. Life satisfaction and the relative frequency of positive and negative emotions are parts of subjective well-being. According to the prospect theory, hedonic adaptation helps to explain why positive emotion is often so hard to be maintained, and negative emotion wouldn’t be easy to be eliminated. So we expect the relationship between income and positive emotion is different from that between income and negative emotion. Given that regional reference is the main comparison mechanism, effects of regional average income on regional average subjective well-being should be potentially zero if only relative income matters. Using multilevel analysis, we tested the hypotheses with a dataset of 30,144 individuals from 162 counties in China. The results suggested that household income at the individual level is associated with life satisfaction, happiness and negative emotions. On the contrary, at a county level, household income is only associated with negative emotion. In other words, happiness and life satisfaction was only associated with relative income, but negative emotion was associated with relative income and absolute income. Without social comparison, income doesn’t improve happiness, but it could weaken negative emotion. Therefore, it is possible for economic growth to weaken negative emotion without improving happiness. These findings also contribute to the current debate about the “Esterling paradox.”